Helicobacter pylori-induced posttranscriptional regulation of H-K-ATPase α-subunit gene expression by miRNA - Zhang, Yong-Mei; Noto, Jennifer M.; Hammond, Charles E.; Barth, Jeremy L.; Argraves, W. Scott; Backert, Steffen; Peek, Richard M.; Smolka, Adam J. (American Journal of Physiology-Gastrointestinal and Liver Physiology, 2014)
Acute Helicobacter pylori infection of gastric epithelial cells induces CagA oncoprotein- and peptidoglycan (SLT)-dependent mobilization of NF-κB p50 homodimers that bind to H-K-ATPase α-subunit (HKα) promoter and repress HKα gene transcription. This process may facilitate gastric H. pylori colonization by induction of transient hypochlorhydria. We hypothesized that H. pylori also regulates HKα expression posttranscriptionally by miRNA interaction with HKα mRNA. In silico analysis of the HKα 3′ untranslated region (UTR) identified miR-1289 as a highly conserved putative HKα-regulatory miRNA. H. pylori infection of AGS cells transfected with HKα 3′ UTR-Luc reporter construct repressed luciferase activity by 70%, whereas ΔcagA or Δslt H. pylori infections partially abrogated repression. Transfection of AGS cells expressing HKα 3′ UTR-Luc construct with an oligoribonucleotide mimetic of miR-1289 induced maximal repression (54%) of UTR activity within 30 min; UTR activity was unchanged by nontargeting siRNA transfection. Gastric biopsies from patients infected with cagA+ H. pylori showed a significant increase in miR-1289 expression compared with uninfected patients or those infected with cagA- H. pylori. Finally, miR-1289 expression was necessary and sufficient to attenuate biopsy HKα protein expression in the absence of infection. Taken together, these data indicate that miR-1289 is upregulated by H. pylori in a CagA- and SLT-dependent manner and targets HKα 3′ UTR, affecting HKα mRNA translation. The sensitivity of HKα mRNA 3′ UTR to binding of miR-1289 identifies a novel regulatory mechanism of gastric acid secretion and offers new insights into mechanisms underlying transient H. pylori-induced hypochlorhydria. © 2014 the American Physiological Society.
Created from Fastlane, Scopus look-up
Keywords: H; H-K-ATPase; MicroRNA; Proton pump; Pylori; Regulation acid secretion